Chaos Bound Orderly Disorder in Contemporary Literature and Science - Hayles, N. Katherine (Cornell University Press, 2018)
N. Katherine Hayles here investigates parallels between contemporary literature and critical theory and the science of chaos. She finds in both scientific and literary discourse new interpretations of chaos, which is seen no longer as disorder but as a locus of maximum information and complexity. She examines structures and themes of disorder in The Education of Henry Adams, Doris Lessing's Golden Notebook, and works by Stanislaw Lem. Hayles shows how the writings of poststructuralist theorists including Barthes, Lyotard, Derrida, Serres, and de Man incorporate central features of chaos theory.